The end of the Pagan city: religion, economy, and urbanism in Late Antique North Africa - Leone, Anna (Oxford University Press, 2013)

Erratum to: Developing a Collaborative Strategy to Manage and Preserve Cultural Heritage During the Libyan Conflict. The Case of the Gebel Nāfusa - Nebbia, Marco; Leone, Anna; Bockmann, Ralf; Hddad, Mftah; Abdouli, Hafed; Masoud, Ahmed M.; Elkendi, Nader M.; Hamoud, Hassan M.; Adam, Salah S.; Khatab, Moncif N. (Journal of Archaeological Method and Theory, 2016)
Keywords: Archéologie – Djebel Nefousa

Developing a Collaborative Strategy to Manage and Preserve Cultural Heritage During the Libyan Conflict. The Case of the Gebel Nāfusa - Nebbia, Marco; Leone, Anna; Bockmann, Ralf; Hddad, Mftah; Abdouli, Hafed; Masoud, Ahmed M.; Elkendi, Nader M.; Hamoud, Hassan M.; Adam, Salah S.; Khatab, Moncif N. (Journal of Archaeological Method and Theory, 2016)
The paper discusses the potential of a collaborative scheme for the development of a protocol for recording and managing the cultural heritage in Libya. The critical political situation in the country urges the development of cultural heritage
Keywords: Archéologie – Djebel Nefousa